2018
DOI: 10.1038/s41598-018-30055-y
|View full text |Cite
|
Sign up to set email alerts
|

AIEC infection triggers modification of gut microbiota composition in genetically predisposed mice, contributing to intestinal inflammation

Abstract: A high prevalence of adherent-invasive E. coli (AIEC) in the intestinal mucosa of Crohn’s disease patients has been shown. AIEC colonize the intestine and induce inflammation in genetically predisposed mouse models including CEABAC10 transgenic (Tg) mice expressing human CEACAM6-receptor for AIEC and eif2ak4−/− mice exhibiting autophagy defect in response to AIEC infection. Here, we aimed at investigating whether gut microbiota modification contributes to AIEC-induced intestinal inflammation in these mouse mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 54 publications
5
41
0
Order By: Relevance
“…108 Bretin and colleagues recently suggested that transient AIEC infection in mice can promote inflammatory signaling after clearance of the pathobiont. 136 These data demonstrate that pathobionts are able to induce stress responses and inflammatory signaling in IECs and may continue to promote inflammation long after infection.…”
Section: Activation Of Immune and Stress Responsesmentioning
confidence: 76%
See 1 more Smart Citation
“…108 Bretin and colleagues recently suggested that transient AIEC infection in mice can promote inflammatory signaling after clearance of the pathobiont. 136 These data demonstrate that pathobionts are able to induce stress responses and inflammatory signaling in IECs and may continue to promote inflammation long after infection.…”
Section: Activation Of Immune and Stress Responsesmentioning
confidence: 76%
“…For example, Helicobacter bilis does not alter microbial composition while adherent-invasive E. coli induces dysbiosis despite commensal-directed immune responses. 135,136 In this section we review the current understanding of various pathobionts in the GI tract.…”
Section: Pathobiont Bacteria and Intestinal Function In Ibdmentioning
confidence: 99%
“…Recently, our group showed that deficiency of the amino acid deprivation sensor EIF2AK4 (eukaryotic translation initiation factor 2 alpha kinase 4) in mice, which leads to impaired autophagy-mediated clearance of CD-associated AIEC and consequently enhanced inflammation [29], induces changes in the fecal microbiota composition upon AIEC colonization but not under the steady state [30]. This suggested that in some conditions, defective autophagy alone does not trigger intestinal dysbiosis but its combination with an infectious agent can do so.…”
Section: Autophagy and Gut Microbiotamentioning
confidence: 99%
“…First, by "spiking in" the EAEC strain into the fecal culture, the a-diversity is of course altered (Fig. 5), not unlike when humans are infected with enteric pathogens, and this has also been demonstrated in mice (62). In contrast, the gut microbiome a-diversity was observed to be reduced up to 40% in patients given ciprofloxacin, a fluoroquinolone commonly prescribed for E. coli infections (16).…”
Section: Discussionmentioning
confidence: 94%